Civil protection of personal electronic data in the Emirati legislation - Alhefeiti, Abdulla Rashed Ali Bin Shahein; Aldahmani, Saif Khamis Mohammed Marzooq; Alyammahi, Alyaa Ali Khameis Rashed; Alzeyoudi, Saadah Saif Saeed Ahmed; Alraeesi, Ahood Abdulla Mohamed Shaml (Research Journal in Advanced Humanities, 2025)
The digital revolution has transformed industries, but privacy protection challenges persist. Countries like the UAE have established legal frameworks for civil liability that balance the benefits of technology with individual rights. However, classification raises issues like contractual breaches, tort liability, and jurisdictional conflicts. Research on civil liability is crucial for ensuring legal certainty and trust. The Protection of Electronic Personal Data is deemed one of the fundamental pillars of digital security in the modern era. It plays an essential role in protecting individuals’ privacy and preventing the misuse of their information for illegal activities, such as fraud and identity theft. Besides, it strengthens the users’ trust in the electronic transactions and supports compliance with local and international laws and regulations related to information security. In fact, its significance extends to protecting community and national security, as data leaks might threaten stability or be used to manipulate public opinion. Therefore, securing data is a basic requirement for achieving safe digital transformation and ensuring that individuals and communities can benefit from electronic services efficiently and with confidence. The current research aims to provide a comprehensive understanding of “Civil Protection of Electronic Personal Data” by examining the national and international legal frameworks that regulate this field, in addition to analyzing the forms of civil liability that would result from violating such data, whether contractual or tortious, along with the resulting legal consequences. Moreover, it seeks to highlight the essential role of this protection in safeguarding the right to privacy, which is fundamental to human dignity, and to evaluate the effectiveness of the available judicial mechanisms that enable individuals to claim compensation for damages resulting from electronic attacks. Finally, this research aims to formulate legislative and practical solutions and proposals to strengthen the civil protection system and enhance individuals' and institutions' awareness of the importance of safeguarding personal data in the digital environment. The legal protection of electronic personal data under UAE Law is considered a pioneering step toward enhancing national security and preserving individual privacy. Federal Law No. 34 of 2021 reflects the state's commitment to keeping pace with technological developments and to addressing risks to personal data. In this study, we have concluded the following key findings and recommendations. Personal Data Protection Law No. (45) of 2021 is an essential step on the right path towards the economic development of the United Arab Emirates in general, and the digital economy and e-commerce in particular. Personal data refers to any information related to identified individuals or those who can be identified through it, such as name, address, national number, and others. Exposing electronic personal data poses risks, necessitating individual awareness and improved security measures. UAE Law penalties deter violations, promote compliance, and raise awareness. Violations of privacy laws result in criminal penalties and civil liability. Victims have the right to request cessation and compensation.